Influence of different raising managements on growth performance, carcass characteristics and meat quality of Muscovy ducks - BOUNPHONG, Soysouvanh; NAOYENG, Khamkeo; SOUKKASERM, Laisone; ONSENG , Sengaloun; KEOHAVONG, Bounmy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study was designed to evaluate the effect of three raising managements on growth performance, carcass characteristics and meat quality of Muscovy duck. Unsexed twenty ducklings were randomly distributed into three housing systems [Free Range (FR), Barn (BA) and Aviary (AV)] at 30 day of age (body weight: 410.33 g/bird). Four different colors labeled (strings) were attached on duckling’s leg (5 bird for each color) as a replicate of the treatment (4 replicates/treatment). A total of 11 weeks of the trial period was taken. Production performance was weekly recorded. Carcass characteristics and meat quality examinations were performed at the end of the trial period. This study shown that the body weight gain and feed per gain were improved in BA (P=0.001), and also increased feed intake (P<0.05). Both internal and external carcass characteristics did not affected by raising managements (P>0.05). Sensory valuation and the value of breast meat color (L*, a*, b*), cooking loss, chilling loss and lymphoid organs did not differ (P>0.05). In contrast, BA shown that the value of pH of raw meat (right breast) after 45 minutes of slaughtering was greater than others (P=0.04), however when storage longer time (24 hours) in the room temperature pH value did not differ (P=0.07). In conclusion, the production performance of Muscovy duck was improved by raising managements, carcass characteristics and sensory values did not affected by raising managements. There’ only the value of pH of fresh meat in BA shown slightly neutral (better), however, we found that when meat storage longer time they became similarly in pH value.